ANALISIS STRATEGI PEMASARAN HOTEL HANGTUAH PADANG - Rahmadani, Ayu (RC-INSTITUT, 2019)
The study aims to determine the marketing strategies of Hangtuah Padang Hotel. This type of research is descriptive qualitative research with survey methods and analyzed using data reduction techniques, data presentation and conclusions which previously found supporting and consistent evidence in the field can answer the formulation of the problem formulated. The informant or sample of this study was HRD Hotel Hangtuah Padang and Sales Marketing at Hangtuah Padang Hotel. Data collection techniques are carried out using observation, interviews and documentation. Furthermore, data analysis techniques use data reduction, data presentation and conclusion. The results of the study are: 1) general findings which are obtained from the hotel history, hotel marketing and hotel uniqueness, 2) special findings obtained by data reduction regarding promotions, products, prices and places 3), available price packages, increasing marketing, publicizing into mass media and online, but there is one disadvantage, that is, the marketing development strategy has not been realized